2016
DOI: 10.3390/sports4020033
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Use and Reasons among the General Population for Using Sports Nutrition Products and Dietary Supplements

Abstract: The purpose of the present study was to determine the prevalence of dietary supplements (DS’s) and sport nutrition product (SNPs) among the general population, to identify differences for gender, age, and exercise frequency, and to determine the main reasons for use. The study was designed as a web-based questionnaire in a representative sample (n = 1544) of the Dutch population. Sixty-two percent (n = 957) of the respondents reported having used DS’s, SNPs, or both in the last twelve months. Women and older p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 22 publications
9
29
0
Order By: Relevance
“…We assessed the use of and reason (i.e., improve health, performance, or both) for consuming 50 pre-specified nutritional supplements (i.e., vitamins/minerals, sports foods, and ergogenic aids) over the last 12 months based on a previous questionnaire of Wardenaar et al ( 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the use of and reason (i.e., improve health, performance, or both) for consuming 50 pre-specified nutritional supplements (i.e., vitamins/minerals, sports foods, and ergogenic aids) over the last 12 months based on a previous questionnaire of Wardenaar et al ( 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Banned supplements, such as caffeine, were reported by 11% (Froiland et al, 2004 ) and 76% (Kristiansen et al, 2005 ) of athletes. Impermissible and banned supplement use is higher among male athletes (e.g., amino acids, creatine, dehydroepiandrosterone often abbreviated as DHEA) while females consumed more permissible supplements (e.g., multivitamin, calcium, and iron) (Froiland et al, 2004 ; Kristiansen et al, 2005 ; Wardenaar et al, 2016 ). Females consumed supplements more for health and males for performance and muscle gains (Froiland et al, 2004 ), yet reasons to consume a particular dietary, sports food, or ergogenic supplement were similar (Wardenaar et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of nutritional supplements to improve performance and augment training adaptations is becoming increasingly prevalent in today’s world of sports and fitness [ 1 , 2 ]. A new class of dietary supplements known as multi-ingredient pre-workout supplements (MIPS) has garnered interest from athletes, fitness enthusiasts, and researchers alike.…”
Section: Introductionmentioning
confidence: 99%
“…However, SDS are no longer reserved only for the professional athletes, but are also used by the general population, including by individuals who try to maintain a fit lifestyle during their everyday activities and careers. A study by Wardenaar et al that was conducted on the general population in the Netherlands showed that two thirds of the questioned group used some sort of supplement (DS, SDS, or both), and that men were more likely to use SDS to enhance physical performance and women were more likely to use DS like vitamins for their health benefits [ 18 ]. Most DS and SDS are easily accessible and they can be bought in most supermarkets, while basic information about them (both true and false) can easily be found on the internet and forums.…”
Section: Introductionmentioning
confidence: 99%